Association between Helicobacter pylori infection and the risk of developing coronary artery disease: a scoping review (Research, Society and Development, 2023)
Helicobacter Pylori (HP) infection affects billions of people around the world, and this bacterium is considered the most prevalent infectious agent in humans. In recent years, the literature has shown a possible association between this infection and the development of coronary artery disease (CAD), since both conditions are considered chronic diseases, sharing similar pathophysiological events. The present study aims to evaluate the association between HP infection and the risk of developing CAD. For this Scoping Review, carried out through the PubMed and Cochrane Library platforms between 2022 and 2012, the chosen descriptors were ''Helicobacter Pylori'', ''Coronary Disease'' and ''Heart'', associated exclusively with the Boolean operator ''AND''. Inclusion criteria consisted of 1) clinical trials, controlled and randomized tests, reviews and meta-analyses, 2) studies on the association between CAD and PH, 3) studies that evaluated the extent of cardiovascular damage due to PH infection and 4) articles written in Portuguese, Japanese, English or Spanish. Exclusion criteria included inadequacies to the theme, case reports and studies with animals, in addition to texts outside the time limit. The evidence found suggested that the main cardiovascular adverse effects related to HP infection were associated with CAD, atherosclerosis, systemic arterial hypertension and acute myocardial infarction. Screening methods, interventional evaluations and indications for the use of laboratory markers, as well as further clinical analysis of this interaction, remain topics to be better elucidated.